Prevalensi Jenis Kelamin dan Usia Pasien Suspek Tuberkulosis (TB) Terhadap Hasil Pemeriksaan Tes Cepat Molekuler (TCM) Menggunakan GeneXpert di RSUD Bahteramas - Darmayanita Wenty; Ani Umar; Heni Umar; Fika (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2025)
Tuberculosis (TB) is one of the infectious diseases that is still a global health problem, including in Indonesia. Examination using Molecular Rapid Test (TCM) is an effective method in detecting TB and resistance to rifampicin. This study aims to determine the prevalence of gender and age of suspected TB patients against the results of TCM examination at Bahteramas Hospital. This study is a quantitative descriptive study with a retrospective approach. Data were obtained from the results of TCM examinations on 309 suspected TB patients conducted at Bahteramas Regional Hospital. The variables analyzed included age, gender, and TCM results, which were categorized as Rifampicin Sensitive (Rif Sen), Rifampicin Resistant (Rif Res), and Negative. The results of this study are that of the 309 patients, the majority were over 46 years old (60.2%) and male (54.4%). The results of the TCM examination showed that 59 patients (19.1%) were detected with rifampicin-sensitive TB, 9 patients (2.9%) with rifampicin-resistant TB, and 241 patients (78%) had negative results. Most patients with positive TB results came from the age group >46 years and were male. The conclusion of this study is that there is a tendency that elderly and male patients have a higher prevalence of positive TCM results. These results indicate the importance of active screening and early detection in certain age groups and genders for TB control.